The choice of payment methods through the lens of behavioral economic - Martinez, Lisana (2024)
The present research analyzes the use of electronic payment methods, specifically debit cards, as a means to pay for essential goods purchases in vulnerable neighborhoods in the city of Bahía Blanca, Argentina. The premise supporting the objective of the study lies in the impact of financial tools in terms of financial inclusion, highlighting the individual and social benefits generated in the economy. Qualitative and quantitative tools are employed under the methodology of behavioral economics, obtaining partial study samples through in-depth interviews and surveys to design behavioral interventions aimed at the use of debit cards for the payment of individuals' regular purchases. The results corroborated that the preferred payment method for individuals is cash, and that there are barriers limiting the use of electronic payment methods. The particular study conducted links structural and behavioral barriers allowing for a behavioral intervention linked to the context in which the purchase takes place. The conclusions obtained after the intervention highlight that although the use of debit cards did not specifically increase, the use of electronic wallets did, allowing the percentage of individuals using cash at the time of paying for their purchases to decrease.